(untitled) (Journal of Laboratory Animal Science, 2024)
The rising incidence of obesity poses a major global health issue, shaped by a complex interaction of genetic, environmental, and behavioral elements. This review focuses on the important function of various animal models in the study of obesity, emphasizing their contributions to comprehending the underlying mechanisms of this intricate condition. Rodent models, especially genetically modified strains such as ob/ob and db/db mice, have revealed crucial insights into the hormonal and genetic pathways that govern energy balance. Furthermore, models of diet-induced obesity and new organisms like zebrafish and C. elegans present innovative methods for investigating the impacts of high-fat diets and genetic differences. The review also ad dresses the limitations of existing animal models, including their in ability to completely mimic the human experience of obesity due to gene-environment interactions and varying metabolic responses. By integrating findings from a range of animal models, this research seeks to deepen the understanding of the causes of obesity and aid in formulating specific therapeutic approaches, ultimately tackling the escalating obesity crisis.